Development of a standardized in vitro model to reproduce hydrophilic acrylic intraocular lens calcification - Britz, Leoni; Schickhardt, Sonja; Yildirim, Timur Mert; Auffarth, Gerd U.; Lieberwirth, Ingo; Khoramnia, Ramin (Scientific reports, 2022)
Opacification through calcification of hydrophilic acrylic intraocular lenses (IOL) is a severe complication after cataract surgery. Causing symptoms that range from glare through to severe vision loss, the only effective therapy is explantation of the opacified IOL so far. Although IOL calcification is a well-described phenomenon, its pathogenesis is not fully understood yet. The purpose of the current study was to develop a laboratory model to replicate IOL calcification. Calcification could be reproduced using a horizontal electrophoresis and aqueous solutions of calcium chloride and disodium hydrogen phosphate. The analysis of the in vitro calcified IOLs was performed using light microscopy, Alizarin Red and Von Kossa staining, scanning electron microscopy, energy dispersive x-ray spectroscopy and electron crystallography using transmission electron microscopy and electron diffraction. The presented laboratory model could be used to identify hydrophilic IOLs that are at risk to develop calcification and to assess the influence of associated risk factors. In addition, it can serve as a research tool to further understand this pathology.
Gesehen am 21.06.2022